(untitled) (Journal of the Bangladesh Agricultural University, 2024)
Drought stress severely affects plant growth and causes huge economic losses worldwide. The beneficial effect of biochar to improve soil properties and plant growth is well discussed nowadays. To investigate biochar’s potential for drought stress mitigation, a two-factorial pot experiment was conducted. Factor one was drought stress (100% Field capacity (FC), 70% FC, and 40% FC) and another was biochar treatment. Cow dung biochar (CDB) and poultry manure biochar (PMB) was applied at three rates (0, 4 and 8 g pot−1). The experiment was designed following a completely randomized design with four replicates. The results showed that drought deteriorated all the studied parameters whereas biochar application significantly improved all the parameters compared to control treatment. The chlorophyll concentration was maximum at the application of CDB as 8 g pot−1 followed by PMB as 8 g pot−1 at both drought conditions (70% FC and 40% FC). Biochar application significantly improved plant height at 28 and 42 days after sowing and the highest plant height was found at the application CDB as 8 g pot−1 followed by PMB as 8 g pot−1. The highest leaflet number was found at the application of CDB at a rate of 8 g pot−1. On average, the root length and biomass at 70% and 40% FC was the highest at the application of 8 g CDB pot−1 which was 28.66% and 61.59% higher, respectively over control. The application of CDB at a rate of 8 g pot−1 increased the shoot biomass by 45.35 and 69.52% compared to control at 70% FC and 40% FC, respectively. Therefore, application of biochar could be an option to reduce drought stress in plants. J Bangladesh Agril Univ 22(3): 317-325, 2024